Roles, Responsibilities and Constraints of Financing Institutions in Fiduciary Law in Indonesia - Nurul Fadhilah (Ipso Jure, 2024)
In the context of an increasingly complex modern economy, the role of financial institutions, especially Fiduciary Guarantees, is crucial in providing and protecting funds for people and companies. Fiduciary Guarantees play a crucial role in consumer financing, especially in the purchase of motor vehicles, by providing legal certainty for creditors and increasing trust in transactions. However, the use of Fiduciary Guarantees often faces obstacles related to legal complexity and procedures, as well as consumer protection and dispute resolution. Research on the role and challenges of financial institutions in applying the Fiduciary Guarantee to customers is relevant to improve the effectiveness of the financial system as a whole. A better understanding of Fiduciary Guarantee registration obligations and procedures is needed to ensure financial institutions' compliance with applicable regulations and to enhance customer protection. This research has the potential to provide better insights on how to improve the efficiency and compliance of financial institutions in applying the Fiduciary Guarantee, which in turn will support sustainable economic growth.